Overcoming the barriers to initiating illegal anabolic steroid use - Maycock, Bruce; Howat, Peter (Taylor and Francis, 2005)
This paper summarizes the self-reported barriers that men overcame prior to initiating illegal anabolic steroid use, and the associated weakening of social controls that restrict anabolic steroid initiation. Data was collected via participant observation of 147 anabolic steroid users and previous users, 98 in-depth interviews with 42 anabolic steroid users and 49 in-depth interviews with 22 illegal dealers. Additional data came from interviews and eight focus groups with gym instructors, personal trainers and health workers, and the monitoring of policy changes and media reports relating to anabolic steroids.The identified barriers included, coping with potential stigma, gathering of credible information and overcoming structural and resource barriers including developing the skills required to administer the drug and gaining a supply source. As these barriers were overcome there was a reduction in the social controls that inhibit the initiation of illegal anabolic steroid use. By understanding the interaction between potential users, social controls and these barriers it may be possible to strengthen the barriers and hence delay or halt the progression to anabolic steroid use. The paper suggests several demand- and harm-reduction strategies that may assist this process.